The Relationship Between Students’ Participation in the Qur’anic Reading and Writing Extracurricular Program and Their Basic Qur’anic Reading Ability at SMP Negeri 27 Padang - Elsa Elsa; Lili Dasa Putri (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2026)
This study was motivated by the low basic ability of students to read the Qur’an, as they are still at the stage of learning the Hijaiyah alphabet, articulation points, and vowel marks. One factor suspected to influence this condition is students’ participation in the Quranic Reading and Writing (BTA) extracurricular activity. This study aims to determine the relationship between student participation and basic Quranic reading skills at SMPN 27 Padang. This study employs a quantitative approach with a correlational design. The sample consisted of 22 students selected using simple random sampling. Data collection was conducted via a questionnaire to measure student participation and through documentation of grades to assess Quran reading ability. Data analysis utilized percentage calculations and the Spearman Rank correlation test. The results of the study indicate that student participation falls into the low category, with a predominance of the “rarely” category, while Quran reading ability remains at the basic level. The correlation test results show a significant relationship with a coefficient value of 0.681, which falls into the strong category. It is concluded that the higher the student participation, the better the Quran reading ability.Keywords: Participation, Quranic Reading and Writing (BTA) Extracurricular Program, Quran Reading Ability.